Shariah Compliance Of House Ownership Financing With Murabahah Scheme (Study Case at Islamic Business Unit of PT Bank CIMB Niaga Tbk) - Zainal, Veithzal Rivai; Sarkan, Yusuf (Online Journal of Research in Islamic Studies, 2017)
This research constitutes a qualitative one of the aimed at studying shariah compliance of House Ownership Financing with murabahah scheme by using four parameters of shariah compliance which consist of those on the implementation of murabahah contract, to fulfillment the maqashid shariah principles on the implementation of murabahah financing, the accounting record of the murabahah financing realization, and the law document of murabahah financing. The result gained from this research could be concluded those are: (1) the implementation of House Ownership Financing with murabahah scheme generally has fulfilled the shariah principles, although there is still the unsuitable sample related to murabahah object, and the promise to give discount of financing installment for the customers; (2) the implementation of House Ownership Financing with murabahah scheme generally has fulfilled the principles of maqâshid shariah; (3) the accounting record of murabahah financing realization generally has fulfilled the shariah principles, however there is still a thing related to the record of murabahah down payment which is unsuitable with PSAK 102; (4) the law document of murabahah financing has fulfilled the pillar (rukn) and requirement (syarth) of murabahah and it does not transgressed the principles of shariah agreement, namely the freedom of making contract (al-hurriyyah), the equality (al-musâwah), the justice (al-‘adâlah), the willingness (al-ridhâiyyah), the balance (at-tawâzun), the benefit (al-manfa’at), the honesty (ash-shidq) and goodwill. Based on the data of observation result, as a whole the implementation of House Ownership Financing with murabahah scheme in Islamic Business Unit of PT Bank CIMB Niaga Tbk belongs to “Good” category, that is in the amount of 88 %.